Dermatological manifestations in PLHIV visiting link ART centre at rural medical college hospital in Western Tamilnadu, India - Vedhanayagam, Mohankumar; Rajagopalan, Rajesh; Govindan, Srinivasahan Karatupalyam; Rajendran, Balamurgan Bhavani (International Journal of Research in Medical Sciences, 2017)
Background: Ever since the early reports of human immuno deficiency infection, it presented as wide range of infectious and non-infectious dermatoses which correlate with the degree of immunodeficiency. Skin assessment remains a vital tool in the diagnosis and management of HIV infection due to relative easiness of examination. Most of skin diseases are amenable to diagnosis by inspection and biopsy. In this descriptive study, we have enumerated in detail the dermatological manifestations of Link ART centre clients. Methods: To analyze the dermatological manifestations in people living with HIV, we undertook a prospective observational study of all PLHIV on ART visiting IRT Perundurai Medical College Hospital link anti- retroviral therapy centre (LAC) during July 2015 to August 2016 with focus to skin manifestations. Results: Among the 140 clients, 22 in 2010, 12 in 2011, 6 in 2012, 51 in 2013, 36 in 2014, and 9 in 2015, 3 up to June 2016 enrolled for follow up. 31 were transferred to nearby ART, Link ART centres during this period as per their request, 4 lost for follow up and 6 deceased after enrolment, finally ninety-nine (39 male; 60 female) were utilizing our centre during the study period. Majority of participants were on ZLN (zidovudine, lamivudine, and nevirapine) regimen, hailing from rural zones, belonged to low or low middle income group, were undertaking farming, cattle rearing. CD4 counts of the asymptomatic clients in the ZLN group noted increase and decrease in the ZLE (zidovudine, lamivudine, and efavirenz), TLN (tenofovir, lamivudine, and nevirapine) group. In the symptomatic clients, decline in the individual and the mean counts except in female ZLN subset. 70% were clinically asymptomatic and 30 % were having some dermatological manifestations. Multiple manifestations were seen in 5 clients during the study period. Dermatological manifestations observed commonly were fungal and viral infections, xerosis/ichthyoses, adverse drug reactions like lipodystrophy, and discoloration of nails. Conclusions: Skin manifestations observed in this study were due to aging and long term cosmetic side effects of highly active antiretroviral therapy (HAART). Lipodystrophy posed significant aesthetic distress in HAART clients. Hence, early management would decrease the most offending cosmetolgical side effects of the disease and drugs. Therapy yields the declining trend in the inflammatory, infectious dermatoses.